Good Tolerance of Citrate Accumulation due to Plasma Exchange among Patients with Acute-on-Chronic Liver Failure: A Prospective, Observational Study - Yuanji Ma; Yan Xu; Fang Chen; Ying Wang; Lang Bai; Hong Tang (Canadian Journal of Gastroenterology and Hepatology)
Aim. To assess the tolerance of citrate accumulation due to plasma exchange (PE) among patients with acute-on-chronic liver failure (ACLF). Methods. A prospective, observational study was conducted among patients with ACLF who received heparin anticoagulation during PE-centered therapy without filtration and dialysis. Citrate accumulation was defined as the value of total calcium (Catot) to ionized calcium (Caion) ratio (Catot/Caion) greater than or equal to 2.5 (Catot/Caion≥2.5). Results. Fifty-four patients were enrolled. The mean age and MELD score were 50.0 ± 11.3 years old and 25 ± 7, respectively. Thirty-three patients had liver cirrhosis. The total 3-month survival rate was 57.4% (31/54). The mean Catot/Caion at the time before PE was 2.05 ± 0.14. Catot/Caion≥2.5 occurred in 100.0% (54/54) and 29.6% (16/54) of patients with mean Catot/Caion of 4.34 ± 1.52 and 2.36 ± 0.32 immediately after PE and 1 hour after PE, respectively, and these levels were much higher than those before PE (p<0.01). However, all values returned to lower than 2.5 by the next morning with no difference from those before PE (2.10 ± 0.14 versus 2.05 ± 0.14, p>0.05). Hypocalcemia (ionized calcium) and mild alkalosis were the main metabolic alterations. No symptoms associated with hypocalcemia occurred. Conclusions. Citrate accumulation is well tolerated by patients with ACLF who receive PE-centered therapy without filtration and dialysis. This study is regeristed with ChiCTR-OOC-17013618.